2007
DOI: 10.1080/00150190701521251
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Dispersion around the Ferroelectric Phase Transition in Partially Deuterated Glycine Phosphite

Abstract: Deuteration effects on the critical relaxation in hydrogen-bonded ferroelectric glycine phosphite have been examined by the measurements of the complex dielectric constants along the ferroelectric b-axis of a series of partially deuterated crystals. The dielectric dispersion for crystals of low deuteration molar fraction was found to be composed of two Cole-Cole types with clearly different relaxation times. The shorter relaxation time shows a nearly classical mean-field exponent and the relaxation time at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The GPI undergoes a continuous phase transition at 225 K from the monoclinic system with space group P2 1 /a → P2 1 in the ferroelectric phase [8]. Deuterium -hydrogen isotopic effect observed in this crystal gives a large T C shift from 225 K for hydrogenated to 322 K for fully deuterated systems [1][2][3][4]. We have shown that deuteration deteriorates GPI crystals homogeneity as evidenced by spatially inhomogeneous nucleation process with different activation energies [9].…”
Section: Domain Wall Dynamics In Dgpimentioning
confidence: 87%
See 1 more Smart Citation
“…The GPI undergoes a continuous phase transition at 225 K from the monoclinic system with space group P2 1 /a → P2 1 in the ferroelectric phase [8]. Deuterium -hydrogen isotopic effect observed in this crystal gives a large T C shift from 225 K for hydrogenated to 322 K for fully deuterated systems [1][2][3][4]. We have shown that deuteration deteriorates GPI crystals homogeneity as evidenced by spatially inhomogeneous nucleation process with different activation energies [9].…”
Section: Domain Wall Dynamics In Dgpimentioning
confidence: 87%
“…Ferroelectrics of similar composition often show wide variations in their characteristic properties [1][2][3][4]. Such variations in ferroelectric properties can be largely attributed to differences in the structural arrangements of domains and distribution of defects within a multidomain crystal sample.…”
Section: Introductionmentioning
confidence: 99%